Incidence of acute pancreatitis among patients with leptospirosis requiring extracorporeal membrane oxygenation (ECMO): a descriptive study - Joselito R Chavez; Romina A Danguilan; Tristan Paulo R Madrigal; Mara Teresa T Panlilio; Aldrich Ivan Lois D Burog (BMJ Open Gastroenterology, 2023)
Background Acute pancreatitis (AP) is an infrequently reported manifestation of leptospirosis. It is more commonly seen in patients with acute respiratory distress syndrome. Despite novel modalities such as extracorporeal membrane oxygenation (ECMO), the mortality rate remains high and whether this is associated with the lung injury caused by the inflammation in AP remains unclear.Objectives and methods A descriptive study was conducted at a tertiary hospital in the Philippines. Primary outcome was defined as the presence or absence of AP. Secondary outcomes were defined as 28-day mortality rate, length of hospital stay, ECMO days, renal replacement therapy (RRT) days, days on mechanical ventilation, presence of local complications of AP and development of nosocomial infections.Results A total of 27 patients were included in the study, and 88.89% (n=24) were men. The mean age for all patients was 33.59±10.22 years. Out of the 27 patients, 19 (70.37%) were diagnosed with AP. Among these 19 patients, one (5.26%) had necrotising pancreatitis and two (10.52%) developed local complications of pancreatitis. Six patients (31.58%) died among those who developed AP, while one (12.50%) died among those who did not. The duration of hospital stay, ECMO, RRT, mechanical ventilation and development of nosocomial infections was also higher in the group who presented with AP.Conclusion AP is an under-reported complication of leptospirosis. Our study demonstrated a higher mortality and morbidity in patients with leptospirosis who developed AP.